A Foresight Study of Autonomous Mobile Robots (AMRs) for Logistics Sector in Malaysia - Chin Jie Qi,; Alina Shamsuddin, (Research in Management of Technology and Business, 2024)
A In recent years, the logistics industry has seen a rise in the incorporation of AMRs to optimize operations. It has become increasingly helpful and promising because of its capacity to travel in an environment without the assistance of mechanical or electrical guiding devices. The purpose of this research study is to investigate how AMRs are being used in Malaysia's logistics industry. The objective is to identify the drivers, problems, and future trends of AMRs in this Sector. The study collects and analyzes data using a mixed-methods approach, including STEEPV analysis and questionnaires. This research aims to help AMRs gain acceptance and be successfully implemented in Malaysia's logistics sector by achieving its objectives. This research entails a comprehensive examination of the factors influencing the adoption of AMRs in the logistics sector, employing the STEEPV analysis framework. Subsequently, this research used SPSS analysis to present the outcomes of AMRs issues and drivers within the logistics sector. The target respondents were selected are the managers of freight forwarders logistics company in Johor. 170 questionnaires were distributed via Gmail, yielding a 45.88% survey return rate, and identified 'Risk and safety' and 'Labour Cost' as the top two drivers. Furthermore, scenario analysis was conducted based on these drivers, yielding four potential future outcomes from 2023 to 2033. This study aims to enhance awareness among future researchers and stakeholders regarding AMR adoption in the logistics industry, with in-depth findings discussed in subsequent sections.